"I need to know if I'm going to die young": Adolescent and young adult experiences of genetic testing for Li–Fraumeni syndrome. Issue 1 (2nd January 2021) - Forbes Shepherd, Rowan; Werner-Lin, Allison; Keogh, Louise A.; Delatycki, Martin B.; Forrest, Laura E.
Abstract: Purpose: This study explored the genetic testing experiences of adolescents and young adults (AYAs; aged 15–39 years) with, or at 50% risk of, an early onset cancer predisposition syndrome: Li–Fraumeni syndrome (LFS). Design: We used interpretive description and conducted semi-structured interviews with 30 AYAs (mean age 25.5 years): 26 with LFS and four at 50% risk. Findings were developed using team-based, inductive thematic analysis. Findings: Participants reported genetic testing uptake to reduce uncertainty about their gene status and to access cancer risk management. Learning their gene status, however, introduced a new uncertainty about living with high multi-organ cancer risk. Participants preoccupied with surviving cancer during diagnostic testing underestimated the implications of LFS. Reliance on family at this life stage complicated decision-making for genetic testing, especially among adolescents. Conclusion: AYAs undergoing genetic testing for LFS have unique support needs based on their life stage and require developmentally appropriate psychosocial care.